POTENSI DAYAH DALAM PENGEMBANGAN EKONOMI SYARIAH - Mahlel Mansur (SYARIAH: Journal of Islamic Law, 2023)
Dayah as a religious institution that has been around for a long time, over time it is expected that dayah or Islamic boarding schools will not only carry out traditional transmission and transfer of Islamic studies, maintenance of Islamic traditions, reproduction of scholars, but also become health education centers, centers for developing appropriate technology for disadvantaged communities. The type of research used in this study is anthropological in nature. The results of this study say that the potential possessed by Islamic boarding schools to develop Islamic economics is at least in three respects, namely (1) Islamic boarding schools as agents of social change in the Islamic economics sector; (2) pesantren as a sharia business laboratory.